Spatiotemporal dynamics of carbon sequestration capacity and its determinants in rubber plantation ecosystems of Hainan Island - Yinghe An; Zhixiang Wu; Runqing Zhang; Xiang Zhang; Zhenghong Tan; Zhongyi Sun (Global Ecology and Conservation)
Net Ecosystem Productivity (NEP) is a crucial indicator of the carbon sequestration capacity of terrestrial ecosystems. However, the mechanisms underlying the spatiotemporal variations in the carbon sequestration capacity of tropical artificial forest ecosystems remain unclear. In this study, we developed a data-driven semi-empirical model using machine learning to simulate NEP in rubber plantations, and extended its application to Hainan Island by leveraging remote sensing and reanalysis data. We analyzed the direct and indirect effects of climatic factors on the NEP using numerical simulations and a Structural Equation Model (SEM). Furthermore, we quantified the impact of rubber plantation area on NEP by calculating the contribution rate. The results reveal that the model accurately captures the trends and seasonality of Gross Primary Productivity (GPP) (R2=0.88, RMSE=1.19 g C m−2 d −1) and Ecosystem Respiration (RECO) (R2=0.87, MSE=0.94 g C m−2 d −1). Over the past 19 years, NEP shows a slight decreasing trend, with higher carbon sequestration during the rainy season than during the dry season. Rubber plantations in the central region primarily act as weak carbon sources, while those surrounding them predominantly function as carbon sinks (carbon sources/carbon sinks ≈ 6.74 %). Among the climatic factors, changes in water conditions exert a dominant influence on NEP variations (−66.03 %); however, different categories of water conditions (precipitation and relative humidity) have opposite effects (negative effects of precipitation and positive effects of atmospheric relative humidity). Additionally, the expansion of rubber plantation cover area contributed to 4.01 % of the changes in NEP. These findings provide a basis for managing and improving carbon sequestration in plantations.